Effect of Carbon Fibers on Some Properties of Sustainable Reactive Powder Concrete - Jalil, Tara Alaa; Aljalawi, Nada Mahdi Fawzi (Engineering, Technology & Applied Science Research, 2025)
Reactive Powder Concrete (RPC) is an advanced type of Ultra-High-Performance Concrete (UHPC) known for its exceptional mechanical and durability properties. It consists of very fine powders, including cement, sand, Silica Fume (SF), Quartz Powder (QP), Superplasticizer (SP), and very low water to cementitious material ratio (w/cm). The effect of Carbon Fibers (CF) on the mechanical properties of the RPC containing nano-AL2O3 is the objective of this study. The CF were added to the RPC with three percentages, 0.5%, 1%, and 1.5% by volume of concrete. Compressive strength, flexural strength, and splitting tensile strength tests were performed. The findings exhibited that the optimal percentage of CF was 1.5%, where the compressive strength at 7, 28, and 60 days increased by 25.26%, 23.07%, and 20.86%, while the flexural strength increased by 56.92%, 52.94%, and 50%. Also, the splitting tensile strength increased by 39.41%, 36.85%, and 34.78%, respectively, in comparison to the reference mixture.